Analysis of the impact of family planning on China’s economy - Huang, Yichen (2019)
The implementation of China’ s one-child policy has been a whole generation, which produces not only the effect of controlling and slowing down population growth but also a very high social cost. This thesis uses CPI, national savings rate, the pension system, healthcare level, per capita disposable income and education level to analyze the impact of family planning on China's economy. After the econometric model, the author comes to a conclusion that the average family size has a negative impact on China's economy. In the regression analysis, family planning has a negative impact on GDP at the significant level of 0.1, it also has a negative impact on GDP growth rate at the significant level 0.1. Family planning in China has reduced the size of the family and has a favorable effect on growth for the Chinese economy. This thesis also introduces the disadvantages of family planning in China. At the end of the article, it also introduces the second-child policy which opened in 2015.